Julia Kristeva’s the Semiotic and the Symbolic Reading of Adrienne Rich’s "Planetarium" and Carol Ann Duffy’s "Havisham" - Alhemeedawi, Mustafa Amjed Jasim; Basim Saadoon, Ahmed (International Journal of Language and Literary Studies, 2023)
This paper sets itself the task of approaching Adrienne Rich’s "Planetarium" from Kristeva’s perspective of semiotics. It is intended here to show dynamics of signifying language as propounded by Kristeva. The study tries to reveal the hidden and neglected aspect of the poem or in Kristeva’s notion, the semiotic aspect. In Kristeva’s terms, language can be expressed through two realms: the symbolic and the semiotic aspects. "Planetarium" is considered a voice of feminist attitude, oppressed voice by the patriarchal society, which in its turn corresponds to the semiotic or the genotext. It is similar in a sense of oppression how women are oppressed and killed. The genotext is also covered by the potentiality of the symbolic aspect. The genotext appears in the form of tone, repetition, rhythm and even spaces as in "Planetarium." Here in the poem of "Planetarium," the kristevian writing is shown in the heavy use of semiotic aspect as a method of revolution towards the patriarchal structures, which are typified in the symbolic aspect of language. The paper concluded that language is not only means of communicating thoughts; an underlying layer of meaning and intentions might be elicited.